Earnings management: Is accrual usage abusive? Auditors perception of accounting practices in Angola - Santos, Pinho, Carlos; Gomes, Santos, Paula; Carla, Martinho, (Edelweiss Applied Science and Technology, 2025)
This research explores auditors’ perceptions regarding earnings management practices in Angola, with a particular focus on the use of accruals as a mechanism for manipulating financial results. The study also aims to identify the accounting areas most affected by such aggressive practices. A quantitative approach, based on a linear regression model, was adopted through a structured survey conducted in 2024 among auditors from the Big Four firms operating in Angola. The results indicate that accruals are perceived to be used at a significant level as a means of manipulating earnings. Revenue and receivables, personnel expenses, and inventories were identified as the most frequently manipulated areas. The findings also support the emphasis of International Auditing Standard (ISA) 240 on revenue as a key risk area for fraud. The study contributes to a better understanding of financial reporting practices in emerging economies. It provides practical insights for auditors, regulators, and other stakeholders, highlighting the need for focused audit procedures in high-risk areas in Angola.